Answer:
2apples
Step-by-step explanation:
Answer:
y= ab if a≠b
Step-by-step explanation:
y/a −b= y/b −a
multiply each side by ab to clear the fractions
ab(y/a −b) = ab( y/b −a)
distribute
ab * y/a - ab*b = ab * y/b - ab *a
b*y - ab^2 = ay -a^2 b
subtract ay on each side
by -ay -ab^2 = ay-ay -a^2b
by -ay -ab^2 =-a^2b
add ab^2 to each side
by-ay -ab^2 +ab^2 = ab^2 - a^2b
by-ay = ab^2 - a^2b
factor out the y on the left, factor out an ab on the right
y (b-a) = ab(b-a)
divide by (b-a)
y (b-a) /(b-a)= ab(b-a)/(b-a) b-a ≠0 or b≠a
y = ab
Answer:
15.1792 or 15.18
Step-by-step explanation:
14.32 timex 6% or .06 is 0.8592. You add .8592 to 14.32 and get 15.1792 or 15.18 :)
A circle equation is :
( x - p )² + ( y - q )² = r², where p and q are coordinates of the center.
The position of the source is : ( - 6, - 4 ) and the range :
r² = 36 ⇒ r = 6